THE PRESSURE GROUPS RELATIONSGIP IN THE ROMANIAN ENERGETIC SECURITY PROBLEM - COSMIN GABRIEL PACURARU (Challenges of the Knowledge Society)
Romania and the European Union started to accord serious attention to energetic security for just a few years. Although the United States warned the European states that they can become energetically dependent of USSR and later Russia, these ignored the national security. In 2004, with Traian Basescu’s rise to power, we can say that Romania elaborated a serious energetic policy, which is updated in accord with the growing changes that intervene on the gas market and in a geopolitical context.